Penta-helix collaboration in West Sumatra's 'Taste of Padang' branding strategy - Pahala Basuki; Elly Yuliawati (Jurnal Studi Komunikasi, 2025)
The "Taste of Padang" polemic serves as an important case study to understand the formation of effective communication between cross-cultural workgroups. This polemic raises the research question, how is the stakeholder communication process in the creation of 'Taste of Padang' as a brand destination for West Sumatra? This research aims to examine the communication process of tourism and creative economy policies (Parekraf) related to ‘Taste of Padang’ as a destination brand for the province of West Sumatra. This research used a case study method, focusing on the communication processes in creating ‘Taste of Padang’. This research delves into information through in-depth interviews with stakeholders from the penta-helix, including the government, academic, business, community, and media sectors. The main results of this study show that the Effective Intercultural Group Communicator Theory (EIWCT) can lead to a good penta-helix communication process when used with a design thinking approach. The establishment of ‘Taste of Padang’ as the destination branding for West Sumatra was decided by consensus to achieve equal participation among the penta-helix, although it did not reach the ideal definition. The government, as the leading sector of the penta-helix, needs to effectively manage cooperative conflict in addressing the controversy regarding the ‘Taste of Padang’ by prioritising open dialogue and collaboration among stakeholders.